Analisis Perlindungan Investor Perusahaan Asing Hyundai di Indonesia dalam Kegiatan Penanaman Modal Asing Beserta Implikasinya - San Mikael Sinambela; Johan Pardamean Simanjuntak; Mima Defliyanti Saragih; Manotar Leryaldo Sinaga; Chairun Nisa; Esra Julita Br Perangin angin; Joy Novi Yanti Lumbantobing (Hakim, 2023)
One way to finance national development is through foreign investment. Before foreign investors invest in Indonesia, there are many factors that must be considered. One of the factors to be considered is the legal protection provided by the state to foreign investors. The purpose of this study is to identify and analyze the legal protection of foreign investment in Indonesia and its impact. This research aims to analyze and explain systematically, factually, and accurately about regulations related to legal protection of foreign investment in Indonesia. In the results of the research, it can be seen that foreign investment in Indonesia is protected by legal regulations contained in the Investment Law. This law provides adequate protection to foreign investors against various risks, including non-commercial risks, in making foreign investment in Indonesia.